**Solution:**

(i) We know that,

The probability of winning of A + Probability of losing of A = 1

And,

Probability of losing of A = Probability of winning of B

Therefore,

Probability of winning of A + Probability of winning of B = 1

0.83 + Probability of winning of B = 1

Hence, probability of winning of B = 1 – 0.83 = 0.17

(ii) We know that,

Probability of winning of B + Probability of losing of B = 1

And, probability of losing of B = Probability of winning of A

Therefore,

Probability of winning of A = 0.49